Methodists and women's education in Ontario, 1836-1925 - Selles, Johanna M. (Johanna Maria), 1952- (McGill-Queen's studies in the history of religion, 1996)
"Johanna Selles documents nearly a century of Methodist education, from the early seminary movement in Upper Canada, through the establishment of ladies' colleges, to the admission of women into the university. She reconstructs what life was like for women at these institutions and highlights changing ideologies, curricula, and views on women's education as well as introducing some of the unique personalities who shaped Methodist higher education." "Selles concludes that by attempting to create an ideal Christian woman through education, Methodist educational structures consciously created and imposed a class-based gender ideology."--Jacket